2022
DOI: 10.3390/su142214724
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Effect of Fiberglass on the Performance of Epoxy Asphalt Concrete

Abstract: Fiberglass prepared from broken waste glass can be used in epoxy asphalt mixtures for performance enhancement and a toughening effect. There is no systematic study on the influence mechanism of the size and the amount of glass fiber on the properties of epoxy asphalt mixtures. The effects of fiberglass on the properties of epoxy asphalt concrete were evaluated using a tensile test, three-point bending test, four-point bending fatigue test and an SEM scanning test. The results verify that the tensile strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Sin embargo, la efectividad de estas fibras varía según el contexto de aplicación dentro de la mezcla asfáltica, siendo las de 9 mm de longitud y una concentración del 5% las que presentan mejor rendimiento. Este descubrimiento subraya la importancia de calibrar el tamaño de las fibras para asegurar la mejora deseada en la resistencia y el efecto de endurecimiento de los compuestos (Wei et al, 2022).…”
Section: Objetivo Específicounclassified
“…Sin embargo, la efectividad de estas fibras varía según el contexto de aplicación dentro de la mezcla asfáltica, siendo las de 9 mm de longitud y una concentración del 5% las que presentan mejor rendimiento. Este descubrimiento subraya la importancia de calibrar el tamaño de las fibras para asegurar la mejora deseada en la resistencia y el efecto de endurecimiento de los compuestos (Wei et al, 2022).…”
Section: Objetivo Específicounclassified
“…A large number of studies conducted by scholars have confirmed that the addition of glass fiber can provide concrete materials with better crack resistance [14][15][16][17], impermeability [18,19], and durability [20][21][22], as well as improving compressive strength [23,24] and sustainability [15,[25][26][27]. Ramadan investigated the mechanical properties, thermal stability, and radiation mitigation capabilities of composites containing glass waste [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the observed outcome showed increased binder proportional to the increase in fibre dosage. However, excessive fibre dosage of more than 0.3% would give a replacement effect to the tougher aggregate, leading to decreased toughness and strength [4][5][6][7][8][9][10][11]. Another example is synthetic polymer fibre, which comes in various products such as polyethylene (PE), polyethylene terephthalate (PET), and aramid.…”
Section: Introductionmentioning
confidence: 99%